ABHD11 Is Critical for Embryonic Stem Cell Expansion, Differentiation and Lipid Metabolic Homeostasis - Liu, Gaoke; Ruan, Yan; Zhang, Junlei; Wang, Xueyue; Wu, Wei; He, Ping; Wang, Jiali; Xiong, Jiaxiang; Cheng, Yuda; Liu, Lianlian; Yang, Yi; Tian, Yanping; et al. (Frontiers in Cell and Developmental Biology, 2020)
Growing evidence supports the notion that lipid metabolism is critical for embryonic stem cell (ESC) maintenance. Recently, α/β-hydrolase domain-containing (ABHD) proteins have emerged as novel pivotal regulators in lipid synthesis or degradation while their functions in ESCs have not been investigated. In this study, we revealed the role of ABHD11 in ESC function using classical loss and gain of function experiments. Knockout of Abhd11 hampered ESC expansion and differentiation, triggering the autophagic flux and apoptosis. In contrast, Abhd11 overexpression exerted anti-apoptotic effects in ESCs. Moreover, Abhd11 knockout disturbed GSK3β/β-Catenin and ERK signaling transduction. Finally, Abhd11 knockout led to the misexpression of key metabolic enzymes related to lipid synthesis, glycolysis, and amino acid metabolism, and ABHD11 contributed to the homeostasis of lipid metabolism. These findings provide new insights into the broad role of ABHD proteins and highlight the significance of regulators of lipid metabolism in the control of stem cell function.